(untitled) (UNED Research Journal, 2018)
The GAM is a small geographic area that concentrates most of the Costa Rican population, but it that does not contain all the biodiversity that makes the country famous. Here I review information on snakes that coexist with humans in the area. From a total of 142 species, 73 occur in the GAM: 21 species dwell in leaf litter (harmless), two are semi-aquatic species (harmless), 16 tree species (13 harmless) and 34 terrestrial species (26 harmless). Only 11 species pose a real danger to human health but, we can coexist with them in peace